Effect of the quenching temperature on the Izod impact strength of polycarbonate - Rouabah, Farid (Materiali in tehnologije, 2014)
In this study, the development of a mathematical model of the effects of free quenching on the Izod impact strength of polycarbonate (PC) has been investigated. Three different thermal treatments were used: the first quenching from the melt state to different temperatures, the second quenching from Tg + 15 °C and, finally, the annealing. The results have shown that an improvement in the impact strength can be obtained after the second quenching at 40 °C. The impact tests experimentally performed on the molding prototypes yield useful data for a particular structural and impact-loading case. But, it is generally not practical, in terms of time and cost, to experimentally characterize the effects of a wide range of design variables. A successful numerical model for the Izod impact strength of polymers can provide convenient and useful guidelines on product design and, therefore, decrease the disadvantages arising from purely experimental trial and error. It is expensive to prepare the samples for the tests. Therefore, it is necessary to develop a mathematical model that will predict the fracture toughness of polycarbonate as a function of the quenching temperature. Mathematical models for the mechanical properties like the tensile strength, Young%s modulus and Izod impact strength as functions of the quenching temperature are not available. There is no sign that they can be built up from a simple theory; a polynomial interpolation was, therefore, used to generate a fracture-toughness model using the data obtained from the experiments. The shifted model represents the Izod impact of the samples as a function of the first- and second-quenching temperatures.
Keywords: Izod impact strength; Izod udarna trdnost; polikarbonat; polycarbonate; quenching temperature; temperatura kaljenja; matematično modeliranje; mathematical modeling